Assessment of the impact of a pedestrian bridge at an urban intersection - Coa, Jherson (2024)
Road designs that prioritize vehicular flow over vulnerable users are common in Latin America. The present investigation evaluates the impact of the inclusion of a pedestrian bridge, in an urban intersection, on pedestrian mobility. Based on the field inspection and video camera recordings, the recurring behavior of pedestrians at crosswalks and desire lines was identified, lines that are often illegal crossings. In addition, the flow and pedestrian density on the observed routes were determined. It was observed that the pedestrian bridge is used by 24% of pedestrian users at the intersection, the rest of pedestrians use the two informal routes and the two formal ones, which indicates a poor urban infrastructure design. Therefore, a safe alternative design of the intersection was made based on the pedestrian desire lines. A proposal of crossing paths and two pedestrian traffic lights was made, which also include removing the current pedestrian bridge. Therefore, the impact of this bridge on pedestrian mobility was evaluated. The evaluation was carried out through a micro simulation with the VISSIM-VISWALK Software. Results indicate that the crossing travel time is reduced from 107.99 seconds with a pedestrian bridge, to 27.52 seconds without a pedestrian bridge. In addition, there is a reduction in the probability of collision, from 15 incidents of low risk and 2 of high risk, to 9 and 0.5, respectively. Therefore, in this type of urban intersection, the pedestrian bridge does not show any improvement to the pedestrian mobility; on the contrary, due to having a larger travel path which brings more travel time, a few users use this infrastructure without any safety benefit. And, with non-significant changes in the design and including traffic devices such as pedestrian traffic lights, there is a significant improvement in terms of mobility and safety.